Critérios de "indianidade": demandas para o reconhecimento oficial e atendimento em políticas públicas - ARIELLY DE OLIVEIRA AMARILLA (2022)
This study aims to analyze the demands for official indigenous recognition and compliance with public policies. This work carries out a historical journey, starting from the republican period, the military regime - a period in which the indigenist policy had a clearly integrationist bias, being created "indicators of indianity", for the determination of identity - until the present time. For an analysis of public recognition policies, an ethnography have been provided in the villages Jaguapiru and Bororó, located in Dourados.